Optical laminate

A three-layer optical laminate structure addresses the challenge of achieving low reflectivity and excellent scratch resistance in anti-reflection films by incorporating specific resin compositions and inorganic fine particles, resulting in improved performance for image display devices.

JP2025068676APending Publication Date: 2025-04-30AICA KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023178611
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing anti-reflection films struggle to achieve both low reflectivity and excellent scratch resistance, particularly when the amount of hollow silica in the low refractive index layer is increased to reduce reflectance.

Method used

A three-layer optical laminate structure is developed, comprising a hard coat resin composition, an optical adjustment layer with high-refractive index inorganic fine particles, and another optical adjustment layer with amine-modified (meth)acrylate, hollow silica, alumina, and a fluorine-based leveling agent, which enhances scratch resistance and reduces reflectance.

Benefits of technology

The optical laminate achieves low reflectivity and excellent scuff resistance, even when subjected to friction with materials like steel wool, while maintaining good visibility and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068676000001
    Figure 2025068676000001
  • Figure 2025068676000002
    Figure 2025068676000002
  • Figure 2025068676000003
    Figure 2025068676000003
Patent Text Reader

Abstract

To provide an optical laminate having a three-layer structure, which is low reflective and has excellent scratch resistance.SOLUTION: Provided is an optical laminate comprising a hard coat layer, an optical regulation layer 1, and an optical regulation layer 2 which are laminated in this order on a substrate film having optical transparency. The optical regulation layer 2 is a cured product of a resin composition comprising a compound having a polymerizable functional group, a photoinitiator, an amine-modified (meth)acrylate, porous silica fine particles, alumina fine particles, and a fluorine-based levelling agent, where the water contact angle of the fluorine-based leveling agent alone is 112° or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical laminate having a three-layer structure that has low reflection of an external light source and excellent abrasion resistance. [Background technology]

[0002] Anti-reflection films are widely used in image display devices such as liquid crystal displays and organic electroluminescence displays, because they have the characteristic of providing good visibility with little reflection of external light sources such as fluorescent lights. In particular, devices such as touch panels, which allow input to be made on the image display surface with a touch pen, are now required to have higher abrasion resistance and scratch resistance.

[0003] A well-known anti-reflection film has a laminated structure that reduces the reflected light itself by canceling out the light reflected on the surface of the anti-reflection layer (low refractive index layer) and the light reflected on the interface between the anti-reflection layer and a layer adjacent to the anti-reflection layer (for example, a hard coat layer or a high refractive index layer). In addition, the anti-reflection layer usually contains hollow silica fine particles together with a binder resin in order to lower the refractive index. For example, an anti-reflection film with a low refractive index layer containing a complex of a multifunctional (meth)acrylate, hollow silica, and a π-conjugated conductive polymer and a dopant has been proposed (Patent Document 1).

[0004] By adopting such a laminated structure, anti-reflection films have come to be widely used in our daily lives. However, when a lower reflectance is required, it is necessary to increase the amount of hollow silica contained in the low refractive index layer, and in this case, there is a problem that the abrasion resistance and scratch resistance of the low refractive index layer are reduced. Therefore, there is room for improvement in order to create an anti-reflection film that can achieve both low reflectance and better scratch resistance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2012-48195 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an optical laminate having a three-layer structure that has low reflectivity and excellent scratch resistance. [Means for solving the problem]

[0007] In order to solve the above problems, the invention of claim 1 provides a hard coat layer, an optical adjustment layer 1, and an optical adjustment layer 2 laminated in this order on a light-transmitting substrate film, the hard coat layer being a cured product of a hard coat resin composition containing a compound (A) having a polymerizable functional group and a photopolymerization initiator (B) (but not containing (C)), the optical adjustment layer 1 being a cured product of a resin composition containing the (A), the (B), and high refractive index inorganic fine particles (C), The optical adjustment layer 2 comprises the (A), the (B), an amine-modified (meth)acrylate (D), hollow silica fine particles (E), alumina fine particles (F), and a fluorine-based leveling agent (G), and is a cured product of a resin composition in which the (G) alone has a water contact angle of 112° or more.

[0008] The invention of claim 2 provides the optical laminate according to claim 1, characterized in that the blending amount of (F) in the optical adjustment layer 2 is 3 to 35% by weight based on the total amount of solids.

[0009] The invention of claim 3 provides the optical laminate according to claim 1, characterized in that the blending amount of (G) in the optical adjustment layer 2 is 10 to 25% by weight based on the total amount of solids.

[0010] The invention of claim 4 provides the optical laminate according to any one of claims 1 to 3, characterized in that the optical adjustment layer 1 has a refractive index of 1.58 to 1.70. Effect of the Invention

[0011] The optical laminate of the present invention has low reflection of external light sources and good visibility, and also has good scratch resistance even when rubbed with a hard material such as steel wool (hereinafter referred to as SW), making it useful as an anti-reflection film for use in image display devices such as touch panels. BEST MODE FOR CARRYING OUT THEINVENTION

[0012] The optical laminate of the present invention is produced using three types of resins: a hard coat resin composition (hereinafter referred to as HC resin composition) for forming a hard coat layer (hereinafter referred to as HC layer), a resin composition for optical adjustment layer 1 (hereinafter referred to as first resin composition) for forming optical adjustment layer 1 (hereinafter referred to as first layer), and a resin composition for optical adjustment layer 2 (hereinafter referred to as second resin composition) for forming optical adjustment layer 2 (hereinafter referred to as second layer). In this specification, (meth)acrylate includes both acrylate and methacrylate.

[0013] The HC resin composition used in the present invention contains a compound (A) having a polymerizable functional group and a photopolymerization initiator (B).

[0014] The compound (A) having a polymerizable functional group used in the HC composition of the present invention is a main component forming the HC layer, and examples of oligomers include urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, polycarbonate (meth)acrylate, acrylic (meth)acrylate, diene (meth)acrylate, etc., which can be used alone or in combination of two or more. Among these, urethane (meth)acrylate (hereinafter referred to as ureac) is preferred because it has excellent scratch resistance due to the cohesive force of hydrogen bonds derived from urethane bonds.

[0015] The ureac can be obtained, for example, by reacting a polyisocyanate with a (meth)acrylate having a hydroxyl group. Examples of the polyisocyanate that can be used include hexamethylene diisocyanate (hereinafter referred to as HDI), isophorone diisocyanate (hereinafter referred to as IPDI), diphenylmethane diisocyanate, tolylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, hydrogenated xylylene diisocyanate, methylcyclohexylene diisocyanate, HDI isocyanurate, and IPDI isocyanurate, and these can be used alone or in combination of two or more kinds.

[0016] Examples of (meth)acrylates having a hydroxyl group used in the urea include, for example, bifunctional trimethylolpropane di(meth)acrylate, glycerin di(meth)acrylate, pentaerythritol di(meth)acrylate, diglycerin di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, dipentaerythritol di(meth)acrylate, and the like, and trifunctional or higher diglycerin tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and the like.

[0017] As the (A) component other than the oligomer, a low molecular weight binder may be used. For example, a (meth)acrylate having a functional group such as an aliphatic, alicyclic, polyether skeleton, hydroxyl group, or amino group, or an acrylamide compound may be used alone or in combination of two or more. For example, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate (hereinafter referred to as DPHA), etc. may be used. The number of functional groups in (A) is preferably 4 to 15, and more preferably 6 to 10. By making it 4 or more functional, sufficient curability can be ensured, and by making it 15 or less functional, defects such as warping due to cure shrinkage can be reduced.

[0018] The photopolymerization initiator (B) used in the HC composition of the present invention generates radicals when irradiated with ultraviolet light or electron beams, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.

[0019] When the (B) is used in an HC resin composition, it is preferable that it contains an α-hydroxyacetophenone type that is less prone to yellowing. Commercially available products include Omnirad 127, Omnirad 184, and Omnirad 2959 (trade name: manufactured by IGM Resins). Among these, Omnirad 2959, which is particularly less prone to yellowing and has excellent scratch resistance, is preferable. In the HC resin composition, the blending amount of (B) per 100 parts by weight of the radical polymerizable component is preferably 0.5 to 15 parts by weight, more preferably 1 to 10 parts by weight.

[0020] The first resin composition used in the present invention contains a compound (A) having a polymerizable functional group, high refractive index inorganic fine particles (C), and a photopolymerization initiator (B).

[0021] (A) used in the first resin composition of the present invention is the same as (A) in the above-mentioned HC resin composition. The amount of (A) in the first resin composition is preferably 10 to 20% by weight, more preferably 12 to 18% by weight, and particularly preferably 13 to 17% by weight, based on the total solid content of the resin composition. By making it 10% by weight or more, sufficient film curing properties can be ensured, and by making it 20% by weight or less, the refractive index of the first layer can be sufficiently increased, thereby lowering the reflectance of the film.

[0022] (B) used in the first resin composition of the present invention is the same as (B) in the HC resin composition described above. However, the film thickness of the first layer is thinner than that of the HC resin layer, and it is easily inhibited by oxygen, so Omnirad127 (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one), which has high reactivity among α-hydroxyacetophenones, is preferred. Omnirad127 has two cleavage sites, whereas most of the usual photocleavage type polymerization initiators have one cleavage site per molecule. Therefore, after cleavage by irradiation with active energy rays, it can react with the polymerizable monomer at multiple sites, so that the reaction curing property is very good, especially in a thin film, and the molecular weight of the polymerization reaction product can be increased. In the first resin composition, the blending amount of (B) per 100 parts by weight of the radical polymerizable component is preferably 5 to 15 parts by weight, more preferably 8 to 12 parts by weight.

[0023] The high refractive index inorganic fine particles (C) used in the first resin composition of the present invention are blended for the purpose of increasing the refractive index of the first layer. Examples of high refractive index inorganic fine particles include titanium, zirconium, cerium, and barium. The form containing the element is preferably a metal oxide, specifically titanium oxide, zirconium oxide, cerium oxide, and barium titanate, and may be used alone or in combination of two or more kinds. Among these, zirconium oxide is preferred from the two points of view of high refractive index and transparency of the coating film.

[0024] The average primary particle diameter of (C) is preferably 5 to 100 nm, more preferably 10 to 50 nm. By making the average primary particle diameter 5 nm or more, dispersibility can be easily ensured, and by making it 100 nm or less, sufficient total light transmittance can be ensured. The average particle diameter is the median diameter (d=50) measured by a laser diffraction / scattering method in accordance with JIS Z8825-1.

[0025] The blending amount of (C) is preferably 75 to 88% by weight, more preferably 78 to 87% by weight, and particularly preferably 80 to 86% by weight, based on the total solid content of the first resin composition. By making it 75% by weight or more, the refractive index of the first layer can be sufficiently increased, and by making it 88% by weight or less, sufficient curability can be ensured.

[0026] The refractive index of the first layer is preferably 1.58 to 1.70, and more preferably 1.60 to 1.68. By making it 1.58 or more, sufficiently low reflectivity can be ensured, and by making it 1.70 or less, sufficient resin curability can be ensured.

[0027] The second resin composition used in the present invention contains a compound having a polymerizable functional group (A), a photopolymerization initiator (B), an amine-modified (meth)acrylate (D), hollow silica fine particles (E), alumina fine particles (F), and a fluorine-based leveling agent (G).

[0028] (A) used in the second resin composition of the present invention is the same as (A) in the HC resin composition described above. However, since the film thickness of the second layer is thin like the first layer, it is susceptible to curing inhibition by oxygen, and since the outermost layer is the surface that comes into direct contact with the outside, it is preferable that the second layer be an alkylene oxide-modified (meth)acrylate with excellent curing properties.

[0029] The alkylene oxide-modified (meth)acrylate preferably contains at least ethylene oxide (hereinafter referred to as EO)-modified (meth)acrylate (a1) derived from pentaerythritol or trimethylolpropane. (a1) has the characteristic that it can improve the curability even in the case of a thin film because it contains an EO chain and regenerates active radicals from peroxy radicals that have lost their polymerization activity due to oxygen inhibition.

[0030] Examples of the (a1) include EO-modified pentaerythritol tri(meth)acrylate, EO-modified pentaerythritol tetra(meth)acrylate, EO-modified dipentaerythritol tetra(meth)acrylate, EO-modified dipentaerythritol penta(meth)acrylate, EO-modified dipentaerythritol hexa(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, and EO-modified ditrimethylolpropane tetra(meth)acrylate, and can be used alone or in combination of two or more. Among these, 4- or more functional ones are preferred from the viewpoint of high reactivity, and EO-modified pentaerythritol tetraacrylate represented by the following formula (1) is particularly preferred. The number of polymerizations (n) of the EO modification is preferably 3 to 10, more preferably 4 to 8, and particularly preferably 4 to 5. [ka] (1) (n=a+b+c+d≒5 in Equation (1))

[0031] The blending amount of (A) is preferably 20 to 40% by weight, more preferably 23 to 36% by weight, and particularly preferably 25 to 35% by weight, based on the total solid content of the second resin composition. By making it 20% by weight or more, sufficient resin curing properties can be ensured, and by making it 40% by weight or less, sufficient SW scratch resistance and low reflection properties can be ensured.

[0032] (B) used in the second resin composition of the present invention is the same as (B) in the first resin composition described above. Since the second layer is also a thin film, it is an α-hydroxyacetophenone type, and Omnirad127 (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propan-1-one) is preferable because it is less susceptible to polymerization inhibition by oxygen. In the second resin composition, the blending amount of (B) per 100 parts by weight of the radical polymerizable component is preferably 1 to 10 parts by weight, more preferably 3 to 8 parts by weight.

[0033] The amine-modified (meth)acrylate (D) used in the second resin composition of the present invention is blended for the purpose of alleviating polymerization inhibition caused by oxygen during ultraviolet curing and improving the degree of curing. (D) is a compound having at least one amino group and at least one acryloyl group or methacryloyl group. In order to avoid curing inhibition caused by oxygen, a method of exposure in an environment of inert gas such as nitrogen is well known. However, in a production process in which the object is transported at high speed, it is said to be difficult to completely eliminate the influence of oxygen attached to the exposed object, and the blending of (D) remarkably improves the curing property. The amino group may be any of primary amino group, secondary amino group, and tertiary amino group, but tertiary amino group is preferable in terms of curing acceleration.

[0034] Examples of the (D) include amino(meth)acrylate, amine-modified aliphatic (meth)acrylate, amine-modified polyether (meth)acrylate, amine-modified polyester (meth)acrylate, amine-modified epoxy (meth)acrylate, amine-modified urethane (meth)acrylate, etc., which can be used alone or in combination of two or more. Among these, amine-modified polyether acrylate is preferred because of its high reactivity.

[0035] The number of functional groups of (D) is preferably 2 to 8, more preferably 2 to 6, and particularly preferably 2 to 4. By setting it within this range, the surface hardness and scratch resistance can be improved without increasing the cure shrinkage. An example of a commercially available product is EBECRYL80 (product name: manufactured by Daicel Allnext Corporation, tertiary amine tetrafunctional).

[0036] The blending amount of the (D) is preferably 0.1 to 3 weight percent, more preferably 0.2 to 1 weight percent, and particularly preferably 0.3 to 0.5 weight percent, based on the total solid content of the second resin composition. By setting it within this range, sufficient scratch resistance can be ensured. The blending amount is preferably 0.3 to 5 weight parts, more preferably 0.5 to 3 weight parts, based on 100 weight parts of (A).

[0037] The hollow silica fine particles (E) used in the second resin composition of the present invention are blended for the purpose of lowering the refractive index of the second layer. (E) are silica particles having cavities containing air with a refractive index of 1 inside, which have the function of lowering the refractive index of the low refractive index layer while maintaining the coating strength of the layer. While the refractive index of solid silica particles is about 1.45, the refractive index of (E) decreases as the occupancy rate of the internal cavities increases, and is about 1.15 to 1.40.

[0038] The primary average particle size of (E) is preferably 5 to 100 nm, more preferably 20 to 80 nm, and particularly preferably 40 to 70 nm. By setting it within this range, good dispersibility can be obtained without impairing the transparency of the low refractive index layer. In particular, if it is 40 to 70 nm, the void occupancy rate can be increased to lower the refractive index while ensuring a shell thickness that does not cause insufficient strength. The average particle size is the median diameter (d=50) measured by a laser diffraction / scattering method in accordance with JISZ8825-1.

[0039] The blending amount of the (E) is preferably 20 to 40% by weight, more preferably 23 to 38% by weight, and particularly preferably 25 to 35% by weight, based on the total solid content of the resin composition. By making it 20% by weight or more, the refractive index can be sufficiently lowered, and by making it 40% by weight or less, sufficient scratch resistance can be ensured. An example of a commercially available product is Sururia 2320 (trade name: manufactured by JGC Catalysts and Chemicals, solid content 20.5%, average primary particle size 50 nm).

[0040] The alumina fine particles (F) used in the second resin composition of the present invention are blended for the purpose of increasing the hardness of the low bending layer and improving the abrasion resistance. The primary average particle size of (F) is preferably 5 to 100 nm, more preferably 10 to 80 nm, and particularly preferably 30 to 60 nm. By making it 5 nm or more, improvement in abrasion resistance can be expected, and by making it 100 nm or less, an increase in haze can be suppressed and sufficient total light transmittance can be ensured.

[0041] The blending amount of the (F) is preferably 3 to 35% by weight, more preferably 5 to 30% by weight, and particularly preferably 8 to 20% by weight, based on the total solid content of the second resin composition. By making it 3% by weight or more, sufficient abrasion resistance can be ensured, and by making it 35% by weight or less, a sufficiently low reflectance can be obtained. An example of a commercially available product is ALMIBK-M146 (product name: manufactured by CIK Nanotech Co., Ltd., solid content 30%, average particle size 50 nm).

[0042] The fluorine-based leveling agent (G) used in the second resin composition of the present invention is blended for the purpose of improving the slip property of the second layer to improve the abrasion resistance, and lowering the refractive index of the second layer to reduce the reflectance. It is preferable that the leveling agent has a reactive functional group capable of polymerizing with the binder resin to form a cured coating film, in that the effect can be maintained for a long time without being lost over time due to bleeding or the like from the cured coating. Even if the leveling agent is the same, in the case of a silicone-based or fluorosilicone-based leveling agent, the scratch resistance may be insufficient.

[0043] The water contact angle of the (G) when cured by itself is 112° or more, preferably 113° or more, and more preferably 114° or more. If the water contact angle of the (G) by itself is 112° or more, sufficient scratch resistance can be ensured when the composition is cured to form a film. Furthermore, the water contact angle of the cured film when the composition is formed is preferably 107° or more. The mechanism by which a high water contact angle improves scratch resistance is not clear, but it is speculated that one of the reasons for this is that when the water repellency is high, the leveling agent is more likely to concentrate on the film surface during the drying and curing process of the coating film, improving slip properties, and as a result, improving scratch resistance.

[0044] The conditions for preparing the cured film for measuring the water contact angle of the (G) alone were as follows. Five parts of an α-hydroxyacetophenone-based photopolymerization initiator (Omnirad2959) were added to 100 parts by weight of the fluorine-based compound in terms of solid content ratio, and the mixture was applied to a PET film so that the thickness after drying was 3 μm. After drying at 80°C for 1 minute, the mixture was cured with ultraviolet light in a nitrogen purged environment. The ultraviolet curing conditions were as follows: an electrodeless UV irradiation device F300S / LC-6B manufactured by Fusion UV Systems Japan was used, with an output of 1200 mW / cm2 and an accumulated light amount of 200 mJ / cm2 with an H bulb; if the photopolymerization initiator is difficult to dissolve in the fluorine-based compound, it may be diluted with a solvent. The contact angle of water and oleic acid was measured according to the sessile drop method of JIS R 3257:1999, and the measurement was performed after dropping (2 μL) at room temperature and leaving it for 30 seconds using a DMs-400 manufactured by Kyowa Interface Science Co., Ltd.

[0045] The blending amount of the (G) is preferably 10 to 30% by weight, more preferably 13 to 25% by weight, and particularly preferably 15 to 22% by weight, based on the total solid content of the second resin composition. By keeping it within this range, sufficient scratch resistance can be ensured.

[0046] To the composition of the present invention, ultraviolet absorbers, antioxidants, adhesion promoters, bluing agents, defoamers, thickeners, suspending agents, antistatic agents, antifogging agents, antibacterial agents, antiviral agents, organic fine particles, and the like may be added as necessary within the range not impairing the performance.

[0047] When applying the HC resin composition, the first resin composition, and the second resin composition, they may be diluted with a solvent to improve the coating properties. Examples of dilution solvents include alcohol-based solvents such as ethanol, n-propyl alcohol, isopropyl alcohol (hereinafter IPA), n-butyl alcohol, isobutyl alcohol, and diacetone alcohol, ketone-based solvents such as acetone, methyl ethyl ketone (hereinafter MEK), methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as ethyl acetate and butyl acetate, and ether-based solvents such as PGM, diethyl ether, and diisopropyl ether, and these can be used alone or in combination of two or more. The solid content when diluted is 1 to 70%, but is not particularly specified and can be appropriately set to a viscosity that is easy to apply.

[0048] Examples of the light-transmitting substrate film on which the HC resin composition is applied include polyester film, triacetyl cellulose film, polycarbonate film, polysulfone film, nylon film, cycloolefin film, acrylic film, polyimide film, ABS film, polyolefin film, PVC film, PVA film, etc. Among them, a biaxially stretched polyester film is preferably used from the viewpoints of weather resistance, processability, dimensional stability, etc. The thickness of the film may be about 25 μm to 500 μm.

[0049] For the purpose of improving adhesion to the HC resin composition, the substrate film may be subjected to a surface treatment such as a primer treatment, a sandblasting method, a solvent treatment, or the like to make the surface uneven, or a surface oxidation treatment such as a corona discharge treatment, a chromic acid treatment, or an ozone / ultraviolet light irradiation treatment.

[0050] The method for applying the HC resin composition, the first resin composition, and the second resin composition is not particularly limited, and they can be formed by a known coating method such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, and wire bar coating, or a printing method such as gravure printing, screen printing, offset printing, and inkjet printing.

[0051] The thickness of the HC resin composition when dry can be, for example, 1 μm to 10 μm, but is not limited thereto. The thickness of the first layer applied on the HC layer when dry is preferably 50 to 200 nm, more preferably 80 to 150 nm. The thickness of the second layer when dry is preferably 50 to 200 nm, more preferably 80 to 150 nm. If the thicknesses of the first layer and the second layer are within this range, it is possible to sufficiently reduce the reflectance of the film.

[0052] Examples of light sources for ultraviolet irradiation used when curing the HC resin composition, the first resin composition, and the second resin composition include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, and electrodeless ultraviolet lamps, and the atmosphere for irradiation may be air or an inert gas such as nitrogen or argon. In addition, the curability can be further improved by heating the back roll or heating the coating film with an IR heater during ultraviolet irradiation. Irradiation conditions include an irradiation intensity of 500 mW / cm. 2 ~3000mW / cm 2 , exposure dose 50-400mJ / cm 2 are given as examples, but are not limited to these.

[0053] The present invention will be described in detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were taken at room temperature of 25°C and at a relative humidity of 65%. The amounts of the ingredients are in parts by weight. EXAMPLES

[0054] HC resin composition 10 parts of ureac (a hexafunctional ureac obtained by reacting HDI with PETA) as (A) and 0.5 parts of Omnirad2959 (product name: manufactured by IGM Resins) as (B) were used, and the mixture was diluted with ethyl acetate and PGM so that the solid content was 40%, and stirred until uniformly dissolved and dispersed to obtain an HC resin composition.

[0055] First resin composition One part of DPHA (product name: Nippon Kayaku Co., Ltd., a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate) was used as (A), 0.1 part of Omnirad127 (product name: IGM Resins Co., Ltd.) was used as (B), and 20 parts of P01 (product name: CIK Co., Ltd., nano zirconia, average particle size 20 nm, solid content 30% by weight) was used as (C), and these were diluted with IPA and PGM (IPA:PGM=1:1) so that the solid content was 3%, and stirred until uniformly dissolved and dispersed. A first resin composition was obtained.

[0056] Second resin composition MT3041 (trade name: manufactured by Toagosei Co., Ltd., tetrafunctional EO-modified acrylate) was used as (A), Omnirad127 (trade name: manufactured by IGM Resins Co., Ltd.) was used as (B), EBECRYL80 (trade name: manufactured by Daicel Allnex Co., Ltd., amine-modified polyether acrylate, solid content 100%, tetrafunctional tertiary amino group compound) was used as (D), Suluria 2320 (trade name: manufactured by JGC Catalysts and Chemicals Co., Ltd., solid content 20.5%, primary average particle size 50 nm, refractive index 1.3) was used as (E), M146 (trade name: manufactured by CIK Nanotech Co., Ltd., solid content 30%, average particle size 50 nm, MIBK dilution) was used as (F), and Fluorine-based 1 (fluorine-based, solid content 20%, reaction As a leveling agent, fluorine-based 2 (fluorine-based, 20% solids, containing reactive functional groups, water contact angle by itself 110°), fluorine silicone-based (20% solids, containing reactive functional groups, water contact angle 112°), and silicone-based (100% solids, containing reactive functional groups, water contact angle 100°) were used in the formulations shown in Tables 1 and 2, and the mixture was diluted with IPA and PGM (IPA:PGM=1:1) to make the solids content 3%, and stirred until uniformly dissolved and dispersed to obtain a second resin composition.

[0057] Table 1 JPEG2025068676000002.jpg103161

[0058] Table 2 JPEG2025068676000003.jpg104150

[0059] The evaluation method was as follows.

[0060] Preparation of HC layer The HC resin composition was applied to a PET film U403 (product name: manufactured by Toray Industries, Inc., thickness 50 μm, with easy-adhesion layer) to a dry thickness of 3 μm, and dried at 80° C. for 1 minute. Then, using an ultraviolet exposure device ECS-151U manufactured by iGraphics Co., Ltd., the coating was exposed to 100 mW / cm 2 ,800mJ / cm 2 The mixture was cured under the above conditions to prepare an HC film.

[0061] Preparation of optical laminates The first resin composition was applied onto the HC layer prepared above so as to give a dry film thickness of 100 nm, and then dried at 80°C for 1 minute. After that, the first resin composition was exposed to ultraviolet light at 100 mW / cm using an ECS-151U ultraviolet exposure device manufactured by iGraphics Co., Ltd. 2 ,800mJ / cm 2 The resulting mixture was cured under a nitrogen atmosphere to form a first layer. The second resin composition was then applied onto the first layer to a dry thickness of 100 nm, and the coating was dried and exposed under the same conditions as for the first layer to form a second layer.

[0062] Refractive index of first layer: Using an Atago Appe refractometer DR-M2, a piece of optical laminate in which the first layer composition was formed on a PET film was set on the prism surface, and the refractive index was measured at 589 nm for the D line using 1-bromonaphthalene as an intermediate liquid.

[0063] Haze: The optical laminate was measured using Haze-GARD2 manufactured by Toyo Seiki Seisakusho in accordance with JIS K7361-1, with 1.0% or less being rated as ◯ and over 1.0% being rated as x.

[0064] Minimum reflectance: Using the above optical laminate, the surface opposite the coated surface was scratched with sandpaper, filled in with a black pigment marker, and then black PET was attached to set the reflectance of the opposite surface to 0%.Then, the reflectance of the HC surface was plotted every 1 nm in the range of 300 nm to 780 nm using a spectrophotometer to measure the minimum reflectance, with 0.8% or less being ◎, 0.8% to 1.0% or less being ◯, and over 1.0% being ×.

[0065] Water contact angle: In accordance with the sessile drop method of JIS R 3257:1999, water was dropped onto the optical laminate at room temperature using a DMs-400 manufactured by Kyowa Interface Science Co., Ltd., and the contact angle after leaving it to stand for 30 seconds was measured. For the normal state, a contact angle of 107° or more was rated as ○, and a contact angle of less than 107° was rated as ×.

[0066] Abrasion resistance: A load of 1000 g / cm2 was placed on steel wool #0000 and moved back and forth 2000 times. When visually observed, no scratches were observed, which was rated as ◯, slight scratches were observed, which was △, and numerous scratches were observed, which was x.

[0067] Evaluation results Table 3 JPEG2025068676000004.jpg101170

[0068] Evaluation results Table 4 JPEG2025068676000005.jpg107163

[0069] The examples were satisfactory in all respects, including coating haze, minimum reflectance, water contact angle, and scratch resistance.

[0070] On the other hand, Comparative Example 1, which did not contain (D), had poor scratch resistance, Comparative Example 2, which did not contain (E), had a high minimum reflectance, and Comparative Example 3, which did not contain (F), and Comparative Example 4, which did not contain (G), both had poor scratch resistance. In addition, Comparative Example 5, which was a fluorine-based leveling agent and had a water contact angle of less than 112° alone, Comparative Example 6, which was a fluorine silicone-based material, and Comparative Example 7, which was a silicone-based material, all had poor scratch resistance, and Comparative Examples 5 and 7 in particular also had low water contact angles. Furthermore, Comparative Example 8, which did not have the first layer, had a high minimum reflectance, and none of them were suitable for the present invention.

Claims

1. A hard coat layer, an optical adjustment layer 1, and an optical adjustment layer 2 are laminated in this order on a light-transmitting substrate film, the hard coat layer is a cured product of a hard coat resin composition containing a compound (A) having a polymerizable functional group and a photopolymerization initiator (B) (but not containing (C)); the optical adjustment layer 1 is a cured product of a resin composition containing the (A), the (B), and high refractive index inorganic fine particles (C), An optical adjustment layer 2 is an optical laminate comprising the (A), the (B), an amine-modified (meth)acrylate (D), hollow silica fine particles (E), alumina fine particles (F), and a fluorine-based leveling agent (G), and is a cured product of a resin composition having a water contact angle of 112° or more for the (G) alone.

2. 2. The optical laminate according to claim 1, wherein the blending amount of (F) in the optical adjustment layer 2 is 3 to 35% by weight based on the total amount of solids.

3. 2. The optical laminate according to claim 1, wherein the blending amount of (G) in the optical adjustment layer 2 is 10 to 25% by weight based on the total amount of solid matter.

4. 4. The optical laminate according to claim 1, wherein the optical adjustment layer 1 has a refractive index of 1.58 to 1.70.

Citation Information

Patent Citations

  • Antireflection film

    JP2012048195A